Tasa intrínseca de crecimiento de Aleurotrachelus socialis (Hemiptera: Aleyrodidae) en yuca Manihot esculenta - Holguin, CM; Carabalí Muñoz, A.; Bellotti, Anthony C. (2006)
The whitefly Aleurotrachelus socialis Bondar (Hemiptera: Aleyrodidae) is one of the most important pests in cassava (Manihot esculenta Crantz) crops in the Neotropics. In Colombia, this is the major pest to the crop in the departments of Cauca, Valle del Cauca and Tolima, causing yield losses in experimental fields of up to 79%. Since 1995, this species has colonized and increased its populations in new varieties and areas where it was a secondary pest before. To estimate the potential of A. socialis to develop populations in new cassava varieties, the biological parameters and the main vital statistics of this pest were evaluated under controlled conditions (25± 2º C, 70±5% HR, 12L:12D) on the varieties Chirosa (Mcol 2066), Ica Armenia (HMC1) and CMC 40. The results indicated that A. socialis females lived for a longer time (6,4 days) on the genotype CMC-40 and showed a higher reproductive potential (33.8 eggs per female). On the contrary, the lowest developmental time (32,72 days) was obtained on the genotype HMC1. The three genotypes showed high survival rates, being highest on HMC1 (89%). The greatest population increase (rm) was found on HMC1 (0,167 day-1) and CMC40 (0,079 day -1). The biological and population parameters obtained constitute a basic tool to elaborate control strategies for A. socialis.